(3QSGdI MeGQ GHf LjT GdSdeGfi GdYcGhis - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3JhcdJ Ydi CejQ GdeDefj Ld PcQg hHg CSJYjf ai LejY GdCehQ ef YHO CejQ GdeDefj Ld PcQ ehdGfG SHMGfg heedhcg gGOi GdeSJLjHjf s
(3BNQgG (B:s
(3Ke fHJOF Hef gh eJdc afbJdge bJd GdcdGe hCbhGekG BNQjf ai GdYPGH hgh MSHi hfYe GdfUjQ GdeYjf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B28s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdJhMjO hGdedd hGdfMds